Penerapan six sigma untuk meningkatkan kualitas pelayanan pada Instalasi Gawat Darurat (IGD) di Rumah Sakit Toto Kabila Bone Bolango - Rasyid, Abdul; Yacub, Fidya Ayustina; Uloli, Hendra (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
RSUD Toto Kabila Bone Bolango is one of two hospitals in Bone Bolango Regency. The hospital provides inpatient, outpatient, and emergency services. Hospital quality can be measured by patient satisfaction. One way to improve the quality of the hospital is to reduce problems that can have an impact on the quality of the hospital. This study aims to measure the level of patient satisfaction, determine the attributes that are prioritised in improving the quality of emergency department services at RSUD Toto Kabila, and make a proposed improvement design. The methods used in this research are service quality (SERVQUAL) and six sigma DMAIC (define, measure, analyse, improve, control). Based on the results of the study, the quality of service has not met the needs and desires of patients, because there are several attributes that have the largest gap value and the smallest sigma value. Some of these attributes will then be made an improvement design using 5W + 1H.